Жанр оповідки в англомовних працях західних теоретиків літератури ХХ — початку ХХІ ст. - Шувалова, М. (Слово і Час, 2021)
У статті розглянуто англомовні праці провідних західних теоретиків літератури ХХ і ХХІ ст. (Брандера Метьюза, Френка О’Коннора, Чарльза Мейя, Сюзан Лохейфер, Мері Рорбергер, Остіна Райта, Яна Ріда, Клер Хансон, Фльоранс Ґоє, Ханни Меретої та ін.) про жанр оповідки, який активно функціонує на літературній арені від XIX ст. і до сьогодні. Проведено діахронічний аналіз основних етапів осмислення жанру, охарактеризовано ключові питання сучасних дискусій, що стосуються рис оповідки, її обсягу, відмінностей від інших прозових жанрів, визначення, виокремлення як самостійного жанру, огляду в аксіологічних та онтологічних контекстах. Розкриття означеної проблематики здійснено шляхом зіставлення різних теоретичних досвідів із застосуванням компаративного та дискурсивного аналізу. The paper is focused on the perception of the short story genre in the western literary theory of the 20th —21st centuries. At the end of the 19th and the beginning of the 20th century, the term 'short story' was a neologism, and its appearance indicated the rethinking of established literary forms. Th is process led to the development of new literary theories. The works of Brander Matthews (“The Philosophy of the Short Story”, 1901) and Frank O’Connor (“The Lonely Voice”, 1962), prominent writers and literary scholars of the 20th century, established academic short story studies in the English-speaking countries. Charles E. May, Susan Lohafer, Mary Rohrberger, Austin Wright, Ian Reid, Clare Hanson, Florence Goyet, Hanna Meretoja, whose major publications are also within the scope of the paper, provided further investigation of numerous issues of the short story genre and other types of short fiction. The works of the mentioned scholars are widely known and serve as a basis for academic courses and as an introduction to the short story theory. Nevertheless, they are rarely considered as one of the possible theoretical perspectives in the relevant Ukrainian research works on a short story, and it gives a reason for a closer look at them. Due to rising attention to the short literary forms, involving different theoretical frames might be beneficial to the development of the discourse. The paper describes the key issues of modern discussions concerning the distinctive features of the short story, its scope, definitions, establishment as an independent genre, and meaning in axiological and ontological contexts. The issue is explored by comparing different theoretical experiences with the use of comparative and discursive analysis.